Towards an FPGA-based edge device for the internet of things - Pinto, Sandro (2015)
With the growing ubiquity of Internet of Things (IoT), myriads of smart devices connect and share important information over the internet. In order to provide connectivity and interoperability of all the existing heterogeneous wireless devices, a full communication stack is proposed by the IoT Architecture Reference Model (IoT-ARM). From the sensor to the cloud, the proposed stack can be implemented on all IoT devices avoiding the battle for the wireless standard that will be adopted. This work in progress paper proposes an FPGA-based edge device for IoT, which uses SoC (System-on-Chip) FPGA technology to offload critical features of the communication stack to dedicated hardware, aiming to increase systems performance.